PENINGKATAN NILAI TAMBAH PRODUK DUPA MELALUI PELATIHAN PENGEMASAN - Sarwoko, Endi; Nurfarida, Iva Nurdiana (Jurnal Pengabdian West Science, 2025)
The problem faced by the small incense business Dewa Harum Sari in Petungsewu Village, Wagir District, Malang Regency, is that its sales performance has not experienced growth from year to year. This problem occurred because Dewa Harum Sari only produces semi-finished incense, and its production is based solely on orders from distributors. The purpose of this community service is to increase income by providing training on how to package incense and produce ready-to-sell products. It is hoped that this solution will increase income because the finished product has a higher added value and is more profitable than semi-finished incense. Product diversification through the sale of fragrant incense products, the home industry Dewa Harum Sari can attract a wider customer base and enhance its brand appeal. The service method uses a community-based participatory approach that involves business owners actively participating in the process from identifying problems to finding solutions. Business owners are also involved in the activities carried out, such as training and assistance in product packaging, which includes label design, packaging design, and variations in packaging contents. As a result of this training and assistance, Dewa Harum Sari can now sell incense under the brand DHS while still selling its main product, semi-finished incense. The initial marketing efforts for this fragrant incense product are currently focused on the Malang Regency area. The product diversification strategy implemented in the community service activities was able to provide solutions in the form of increased sales and increased income.